The Role of a Multilingual Environment in the Acquisition of Arabic as a Second Language: A Case Study at Pondok Modern Arrisalah Ponorogo - Lintang Luthfi Kirani; Ruhamauliyah Meiliyati; Abdul Munip (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2026)
This study aims to analyze the role of a multilingual environment in the acquisition of Arabic as a second language at Pondok Modern Arrisalah Ponorogo. The multilingual environment, which involves the use of Arabic, English, and Indonesian, represents an interesting linguistic phenomenon to be examined from the perspective of second language acquisition. This research employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, involving students, Arabic language teachers, and language coordinators as research participants. The findings indicate that the multilingual environment at Pondok Modern Arrisalah is systematically developed through language policies, structured language programs, and the habituation of language use in students’ daily lives. This environment plays a significant role in supporting the acquisition of Arabic, particularly through the intensity of language exposure, social interaction, and continuous communicative practice. The presence of other languages does not entirely hinder the process of Arabic acquisition; rather, in certain contexts, it functions as scaffolding that helps students understand and strengthen their linguistic competence. The main supporting factors include the consistency of language policies, teachers’ role modeling, and students’ motivation, while the inhibiting factors include differences in students’ linguistic backgrounds, low self-confidence among some learners, and the influence of non-target language use